Spectral Database of Pharmaceutical Common Excipients and Paracetamol API Using ASD Field Spec 4 Spectrordiometer (Medico Legal Update, 2021)
Adulteration in pharmaceutical products is common all over the world particularly in pharmaceutical oraldosage forms like tablets, gelatin capsules. According to previous studies there were many techniquesare available to recognize counterfeit medicines. Near Infrared Spectroscopic techniques is widely usedin this area due to its numerous advantages. In this work, we used ASD Field Spec4 Spectroradiometerhaving broad spectral range (350-2500 nanometer) and its supporting software’s to create Spectral libraryof pharmaceutical common drug Paracetamol and some basic excipients used in pharmaceutical industryas formulation process of tablets and capsules and finally also showed the absorption bands of ParacetamolAPI and Excipients.